The Influence of Brand Image and Brand Trust on Consumer Loyalty (Case Study on Consumers of PT Citilink Indonesia Branch Office Denpasar) - Aditya Aristana, I Komang Gede; Arie Yudhistira, Putu Gde; Sasmita, M. Tanggap (Institut Pariwisata Trisakti, 2022)
This study aims to determine the effect of brand image and brand trust on consumer loyalty. This type of research is quantitative research. This research method uses multiple regression analysis. Data collection techniques using questionnaires, sampling techniques using a purposive sampling technique. The population in this study were domestic passengers of PT Citilink Indonesia Denpasar Branch Office in the last five years. The sample used the slovin formula with 100 respondents. The results showed that partially and simultaneously, the variable brand image and brand trust significantly affected consumer loyalty. The brand image formed by Citilink airline can provide a good perception to consumers and the existing efforts in building brand trust in consumers through fulfilling the needs desired by Citilink airline consumers. PT. Citilink is expected to improve its brand image further and maintain and increase the confidence of existing brands by always providing the flight services that consumers want so that consumers no longer doubt the service products that PT has produced. Citilink. Then also pay attention to consumer loyalty; for example, companies can more quickly evaluate what consumers want by providing criticism and advice services to Citilink airlines. Keywords: Customer Loyalty, Brand Image, Brand Trust